Rapid, Cost-Effective Application of Tibilia TB Rapid Test for Culture Confirmation of Live and Heat-Killed Mycobacterium tuberculosis - Ngeow, Yun Fong; Wong, Yan Ling; Ng, Kee Peng; Ong, Chia Sui; Aung, Wah Wah (American Society for Microbiology (ASM), 2011)
Tuberculosis (TB) diagnostic laboratories face many challenges in their obligation to provide rapid, accurate reports that can help clinicians to make therapeutic decisions. One important procedure in TB diagnosis is the confirmation of an acid-fast isolate as Mycobacterium tuberculosis. This is because nontuberculous mycobacterial (NTM) species are increasingly being associated with clinical infections (2, 3). These NTM species are resistant to first-line anti-TB drugs and, when mistaken for M. tuberculosis, give rise to erroneous identification of multidrug-resistant TB (MDR-TB).